Weekly versus every-three-weeks platinum-based chemoradiation regimens for head and neck cancer - Melotek, James M. (J Otolaryngol Head Neck Surg, 2016)
BACKGROUND: The majority of chemoradiation (CRT) trials for locally advanced head and neck squamous cell carcinoma (HNSCC) have relied on platinum-based chemotherapy regimens administered every-3-weeks. However, given the increased utilization of weekly platinum regimens, it remains unclear how different chemotherapy schedules compare regarding efficacy and toxicity. METHODS: We retrospectively identified 212 patients with HNSCC who were treated at a single academic medical center with concurrent platinum-based CRT given weekly (N = 68) or every-three-weeks (N = 144). JMP version 10 (SAS Institute) was used for statistical analysis. Discrete variables were compared with the chi-square test and differences in the medians were assessed using the Wilcoxon test. Survival curves were constructed using the Kaplan-Meier method and significance was assessed using the log rank test. For univariate analysis and multivariate analysis, we used Cox proportional hazard or logistic regression models to compare differences in survival or differences in categorical variables, respectively. RESULTS: Patients receiving weekly platinum regimens were more likely to be older (median age 61.4 vs. 55.5 y; P < .001), have high or very high Charlson comorbidity index (45.6% vs. 27.8%; P = .01), and receive carboplatin-based chemotherapy (6.3% vs. 76.5%; P < .001). Weekly and every-3-week platinum regimens had similar locoregional control (HR 1.10; 95% CI 0.63–1.88; P = .72), progression-free survival (HR 1.13; 95% CI 0.75–1.69; P = .55), and overall survival (HR 1.11; 95% CI 0.64–1.86; P = .71). Every-3-weeks platinum regimens were associated with increased days of hospitalization (median: 3 days vs. 0 days; P = .03) and acute kidney injury (AKI) during radiotherapy (50.0% vs. 22.1%; P < .001). On multivariate analysis, AKI was significantly associated with every-3-weeks regimens (OR: 24.38; 95% CI 3.00–198.03; P = .003) and high comorbidity scores (OR: 2.74; 95% CI 2.15–5.99; P = .01). CONCLUSIONS: Our results suggest that every-3-weeks and weekly platinum-containing CRT regimens have similar disease control but weekly platinum regimens are associated with less acute toxicity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40463-016-0175-x) contains supplementary material, which is available to authorized users.